2013
DOI: 10.5847/wjem.j.issn.1920-8642.2013.02.007
|View full text |Cite
|
Sign up to set email alerts
|

CoolClot, a novel hemostatic agent for controlling life-threatening arterial bleeding

Abstract: BACKGROUND:Uncontrolled bleeding is the first leading cause of preventable death in the battlefield and the 2nd cause of mortality in civil accidents. Incompressible hemorrhage control is among the interventions that drastically increase the survival rate in wound individuals. We have previously shown that a certain mixture of bentonite and zeolite minerals can significantly decrease the bleeding in rats.METHODS:In this study, nine healthy hybrid dogs were selected and after induction of anesthesia with ether,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The lowest coagulation time of about 140 ± 2 seconds was obtained for pearlite with a powder concentration of 50 mg mL −1 , while this time was longer for other powders (control: 315 ± 2 seconds, kaolin: 192 ± 5 seconds, and bentonite: 202 ± 4 seconds for 50 mg mL −1 ). Mortazavi et al , 40 showed that the mean coagulation time in control blood samples was 253.4 seconds, whereas it was 149.5, 162.3and 143.4 seconds, respectively in blood samples treated with bentonite, zeolite, and CoolClot (bentonite–zeolite minerals).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lowest coagulation time of about 140 ± 2 seconds was obtained for pearlite with a powder concentration of 50 mg mL −1 , while this time was longer for other powders (control: 315 ± 2 seconds, kaolin: 192 ± 5 seconds, and bentonite: 202 ± 4 seconds for 50 mg mL −1 ). Mortazavi et al , 40 showed that the mean coagulation time in control blood samples was 253.4 seconds, whereas it was 149.5, 162.3and 143.4 seconds, respectively in blood samples treated with bentonite, zeolite, and CoolClot (bentonite–zeolite minerals).…”
Section: Resultsmentioning
confidence: 99%
“… 39 Mortazavi et al showed that a specific mixture of bentonite–zeolite minerals has a significant effect in shortening the bleeding time and can also significantly reduce the blood clotting time. 40 Kaolin is prepared as a bioceramic from the family of layered aluminosilicates [Al 4 (Si 4 O 10 )(OH) 8 ] from the weathering of the feldspar mineral group. 25 Kaolin, an aluminum phyllosilicate clay mineral, is a potent cation-based activator of the intrinsic pathway of coagulation.…”
Section: Introductionmentioning
confidence: 99%
“…Wedmore et al 17 also showed that Celox was successful in all cases of wounds where gauze packing has failed, and homeostasis was established wherever physicians could clearly see the dressing. The results of a study by Mortazavi et al 18 showed the effect of the Cool Clot coagulation factor in reducing the time required to stop bleeding in the animal model of dogs and reducing the time of clot formation in human blood samples. Nouri et al 19 stated that calcium sulphate and ferric sulphate could control hepatic hemorrhage and are effective hemostatic agents in controlling hepatic hemorrhage in the animal model.…”
Section: Discussionmentioning
confidence: 99%
“…Intense exercise has been associated with luteal phase defects and menstrual dysfunctions, with athletes engaging in vigorous exercise more likely to experience oligomenorrhea and amenorrhea. Conversely, moderate exercise is slightly associated with longer menstrual periods [32] .…”
Section: Over Exertionmentioning
confidence: 94%